Pengalaman Siswa Mengikuti PJJ Menggunakan Google Classroom Selama Pandemi Covid-19 - Sri Maisaroh (Reslaj : Religion Education Social Laa Roiba Journal, 2022)
Distance Learning (PJJ) is the best solution to suppress or break the chain of transmission of the covid 19 virus. PJJ itself must be supported by an application that can be used on a cellphone or laptop. One application that is easily accessible and free is Google Classroom (GC). Google Classroom is a learning application issued by Google in learning. Ease of access via computers and mobile phones, is very beneficial for teachers and students. The purpose of this study was to gain an understanding of information about the experiences of students participating in PJJ using google classroom during the covid 19 pandemic. This study used a qualitative approach with the phenomenological method. Data retrieval using online interviews with two class XII students of Refrigeration and Administration Engineering (TPTU), consisting of one student in first rank and the second being the last ranked student in his class. Researchers found strengths and weaknesses in using the Google Classroom application. The strength of Google Classroom is that it is free, the application is easy to download on any device and has features to support learning. The weakness is that the capacity of the class maker in this case the teacher must be large because student assignments are directly stored on the drive and the interaction between teachers/students only uses writing. Keywords: Covid-19, Distance Learning (PJJ), Google Classroom